Upaya Pelestarian Sike Rebana di Sanggar Teratai Putih Desa Kemantan Kebalai Kecamatan Air Hangat Timur Kabupaten Kerinci - Renthy Tri Deviani; Ardipal (EDUMUSIKA, 2024)
This research aims to describe the Sike Rebana preservation system at Sanggar Teratai Putih. This research is classified as qualitative research and the method used is descriptive analysis. The research instrument is the researcher himself as the main instrument. Data collection was carried out through the stages of literature study, observation, interviews, and audio and video recording. Sike Rebana is one of the traditional Kerinci arts developed at the Teratai Putih Art Studio. Researchers examined how conservation efforts include efforts to protect sike art, efforts to develop sike art and efforts to utilize sike art at the Teratai Putih Art Studio. The results of this research are that Sanggar Teratai Putih preserves Sike Rebana in three ways, namely: 1) Protection. Efforts to protect Sike Rebana are carried out by holding Sike Rebana training at Sanggar Teratai Putih. 2) Development, Sike Rebana art has now been developed by artists in Kerinci Regency, especially in Kemantan Kebalai Village, both in terms of quality and quantity. 3) Utilization, Sike Rebana is often used to fill traditional events in Kerinci Regency. White Lotus Art Studio is often invited to perform at MTQ events, city/provincial birthdays, weddings, music festivals and other music events.